Personnel management in Nigeria : a work-centred approach - Aina, Olusola (Ikeja : Edition F Communications, 1992)
Part 1 of this book introduces the reader to personnel management system in Nigeria. Part 2 highlight the basic issues involved in staffing an organization. Part 3 deals with the major issues involved in developing and rewarding of employees. While the final part 4 deals with working with unions.
Includes bibliographical references and index.
hza 13/07/2018
Loans
Keywords: personnel management; Nigeria